Pengaruh Kegiatan Kreasi Kriya Terhadap Keterampilan Motorik Halus Anak ADHD di Kelompok B2 PAUD Terpadu Al-Furqan Jember - Esa Dewi Setyawati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the effect of craft activities on the fine motor skills of ADHD children in Group B2 of Al Furqan Integrated PAUD Jember. The background of this study is based on the still low fine motor skills of ADHD children as seen from the difficulty in coordinating finger and hand movements in daily activities. The research method used is Single Subject Research (SSR) with an A-B-A design. The subject of the study was one child diagnosed with ADHD. Data collection techniques were carried out through observation using fine motor skills assessment instruments. Data were analyzed using visual analysis within and between conditions. The results of the study showed an increase in fine motor skills after being given intervention in the form of craft activities such as forming Clay and stringing. This can be seen from the increase in scores in the intervention phase (B) compared to the baseline phase (A1), as well as a stable tendency in the A-2 phase (A2). Thus, it can be concluded that craft activities have a positive effect on improving the fine motor skills of ADHD children.
Finalisasi Repo 23 Juni 2026_Yudi
Keywords: Craft Creation; Fine Motor Skills; ADHD; Keterampilan Motorik Halus Anak; Kegiatan Kreasi Kriya